Protracted neurobehavioral and microRNA deficits by acute nicotine dependence in mice - Kim, Baeksun; Im, Heh-In (Nature Publishing Group, 2024)
Acute dependence to nicotine can rapidly elicit withdrawal symptoms. However, protracted withdrawal signs from acute nicotine dependence have not been explored. Here, we demonstrate that acute nicotine dependence induces delayed neurobehavioral defects in mice. Acute nicotine dependence led to impairment in passive avoidance but without changes in innate anxiety or learning/memory. Concurrently, F-actin level in the dorsal striatum was aberrantly increased, striatal dendritic spine density was reduced, and striatal neural population activity was diminished after acute nicotine dependence. The smoking-related and synapse-associated microRNA miR-27b was decreased in the dorsal striatum throughout the protracted phase of acute nicotine dependence. In silico analysis with empirical validation revealed the neuronal membrane-associated gene Marcks as a direct inhibition target of miR-27b, and that striatal Marcks was aberrantly enhanced after acute nicotine dependence. Our data collectively indicate that acute nicotine dependence accompanies a series of protracted neurobehavioral sequelae with striatal structural, electrophysiological, and molecular dysfunctions. Early nicotine withdrawal causes a long-lasting impairment in passive avoidance, accompanied by aberrant changes in microRNA, neural activity, and dendritic spines in the dorsal striatum.